ISOLATION AND SELECTION OF CANDIDATES ISOLATE CELLULOLYTIC PROBIOTIC BACTERIA FROM THE LARGE INTESTINE OF BALI PIGS - I G., Pande; Mudita, I M.; Cakra, I G.L.O. (Jurnal Peternakan Tropika; Vol 12 No 1 (2024): Vol. 12 No. 1 Tahun 2024; January - February, 2024)
This research aims to isolate and select superior cellulolytic probiotic bacteria candidates with high degradation ability and antimicrobial activity from the large intestine of Bali pigs. 14 isolates of pure cellulolytic bacteria obtained from the large intestine of Bali pigs were further selected to obtain probiotic cellulolytic bacteria candidate isolates through a test of ability as a probiotic candidate, namely a test of the ability to grow at various temperature variations (10, 25, 40, 55°C), pH (3.5; 4.5; 5.5; 6.5; 8.0), and bile salts (10, 20, 30 µl). Isolates that can grow at various temperatures, pH, and bile salts are categorized as candidates for cellulolytic probiotic bacteria. The quality selection of candidate isolates of cellulolytic probiotic bacteria is based on the ability of substrate degradation (CMC) and the ability to inhibition against pathogenic microbes (E. coli). All activities were carried out with 4 repetitions to obtain representative results. There were 5 isolates of cellulolytic bacteria with codes A5, A11, B2, C11, and C12 which showed growth at various temperatures, pH, and bile salts, so they could be categorized as probiotic candidates. Based on the substrate degradation ability test, the clear zone with the widest diameter was obtained by the isolate with code C12 on the CMC substrate. While in the antimicrobial activity test the widest clear zone was produced by isolate with code C11. Based on the results of the study, 5 candidate isolates of cellulolytic probiotic bacteria from the large intestine of Bali pigs and isolates with codes C11 and C12 could degrade substrates and have higher antimicrobial activity than other isolates.